2001
DOI: 10.1063/1.1398604
|View full text |Cite
|
Sign up to set email alerts
|

Bright pure blue emission from multilayer organic electroluminescent device with purified unidentate organometallic complex

Abstract: Multilayer organic electroluminescent devices (OELDs) were fabricated with highly pure 2-(2-hydroxyphenyl)benzoxazolato lithium (LiPBO), which was obtained through stepwise purification process, as a blue emission layer. The ionization potential of the carefully purified LiPBO was ∼5.82 eV. The multilayer OELD with a hole-blocking layer (HBL) emitted almost pure blue light with the CIE color coordinate of x=0.15 and y=0.08. However, the emission color was redshifted when an electron-transporting layer (ETL) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…Much progress has been made in the development of blue color OLEDs displays. Many materials have been synthesized and used in blue OLEDs, such as distyrylarylene derivatives (DSA) [2], hydroxyphenyl-pyridine beryllium complex [3], unidentate organolithium complex [4], bistriphenylenyl [5], spirobifluorene-cored conjugated compounds [6], and anthracene derivatives [7][8][9]. In these anthracene derivatives, 9,10-di-(2-naphthyl) anthracene (ADN) is one of the most promising blue fluorescent materials for its color purity and thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…Much progress has been made in the development of blue color OLEDs displays. Many materials have been synthesized and used in blue OLEDs, such as distyrylarylene derivatives (DSA) [2], hydroxyphenyl-pyridine beryllium complex [3], unidentate organolithium complex [4], bistriphenylenyl [5], spirobifluorene-cored conjugated compounds [6], and anthracene derivatives [7][8][9]. In these anthracene derivatives, 9,10-di-(2-naphthyl) anthracene (ADN) is one of the most promising blue fluorescent materials for its color purity and thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the different multilayer structures for RGB colors give rise to complicate device fabrication processes which need numerous steps to change and realign shadow masks leading to increased total average cycle time for manufacturing displays, even though multilayer device structures have been considered inevitable in a viewpoint of injecting, transporting, and blocking charge carriers ͑holes and electrons͒ in devices. [6][7][8] Recently it has been reported that the device performance and lifetime was improved by doping an electrontransporting material ͑ETM͒ into a hole-blocking layer, 9 which further provides the possibility of reducing the number of organic layers that contact an electron-injecting layer ͑EIL͒ or cathode by mixing ETM and hole-blocking material. Hence this concept delivers that the anode side functional layers such as hole-injecting layer ͑HIL͒ and holetransporting layer ͑HTL͒ could be made into a single layer, namely a hole-injecting-transporting layer ͑HITL͒ ͑see Fig.…”
mentioning
confidence: 99%
“…This process is sensitive to the molecular environment ͑such as aggregation͒ and impurities. Several blue light emitting organic materials such as poly͑fluorene͒, 1 poly͑N-vinylcarbazole͒, 2 spirobifluorene-cored materials, 3 as well as organometallic, 4 anthracene, 5 and pyrene derivatives, [6][7][8][9] have been used as the emitters. One potential advantage of using conjugated polymers over small molecules is that thin films can be more readily obtained by solution processing.…”
mentioning
confidence: 99%